TALAK TIGA DI LUAR PENGADILAN PERSPEKTIF HUKUM ISLAM DAN HUKUM POSITIF BAGI PEGAWAI NEGERI SIPIL (Studi Analisis Putusan Pengadilan Agama ArgamakmurNomor 0207/Pdt.G/2015/PA.AGM) - Jayanti, Hepi Duri (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
In the case number 0207  / Pdt.G  / 2015  / PA.AGM, it is known that a husband who has a government employees status has directly uttered Talak 3 to his wife, after that, he applied  for divorce to the religious court Argamakmur without attach- ing permission  of divorce  from superiors.  Furthermore, reading  the verdict of the judges of the Argamakmur Religious Court who granted  the petition  for divorce  of the Petitioner,  but did not include  the fact that the Petitioner  had  dropped Talak 3 to his wife before the husband applied  for divorce to the Religious Court and did not attach  the divorce permit from his superior. While it is clear that there is a legal difference between  the Talak 1 and the Talak 3. In addition, the absence of a divorce permit from the competent authority  will result in the Petitioner  being punished with severe discipline based  on the discipline regula- tions of civil servants.  Based  on the above  background, this research  reveals two issues, namely  first how is the legal power of Talak 3 appellation according  to Islamic law and positive law. Second, what is the benefit of divorce certificate for government employees who  filed for divorce  in Religious Court?  This type  of research  is normative juridical research  or library research which is then described descriptively. The results of this study conclude  that the legal power of Talak 3 appellation outside  the courts according  to Islamic law is valid. Because  in Islamic law (the Qur’an  and  hadith)  no one  arranges  if divorce  should  be pronounced in court. Even Talak does not need  a witness when the husband said it; Talak also can be spoken  by husband and firmly or with satire language. But the cancellation  of divorce  cannot  be done  as well as Talak 3 without  going through  Talak1 and  Talak 2. Whereas  according  to Law Number  1 Year 1974,  the appellation of divorce must be done  in front of the court, otherwise  the divorce is not legally recognized  by the state. And among  the husband and wife are still legally bound state even though  according  to Islamic law is not husband and wife anymore. While divorce permits from government employees superi- ors only can be used by the government employees who seek divorce to a religious court. The benefit of the divorce permits for the government employees is to avoid  disciplinary punishment in accordance with applicable  provisions.  Then  if the divorce request  has not been  submitted to a religious court, then  the government employees concerned may be strived for peace  by the team  or direct superior,  so the process  of divorce  proceedings is not necessary, this means  saving time and  money. If the divorce  proceedings continue, the divorce  papers  can  be useful as a basis for judicial consideration in the judgment, as the divorce papers  are the result of a team’s recommendation that examines the reasons  for divorce to obtain  a divorce certificate for the government employees